Low bit rate video coding for remote desktop operation of CNC milling - Maarif, Haris Al Qodri; Gunawan, Teddy Surya; Afzeri, Afzeri (Trans Tech Publications, Switzerland, 2011)

(untitled)
Scalable Video Coding (SVC) is the extension of the H.264/AVC standard. The SVC has good capability in video transmission systems because of its scalability which can adapt in different network conditions, especially in low bit rate transmission. The objective of this paper is to develop the low bit rate video coding for assisting the remote operation of Command and Control (CNC) milling process through virtual simulation and remote desktop interface. The algorithm for low bit rate video coding will be in the downsampling of high resolution layer before the encoding process and upsampling the high layer data in the decoder. Based on simulation results, the proposed scheme shows good performance in maintaining the video quality at 128 kbps while providing high time savings for the encoding process.